Bifurcation and chaos of BNNT-reinforced piezoelectric plate under complex load. (28th January 2021) - Yang, Jinhua; Fu, Guo; Sun, Gaofeng
Abstract: By employing piezoelectric theory with thermal effects and von Kármán nonlinear plate theory, the constitutive equations of the boron nitride nanotube (BNNT)-reinforced piezoelectric plate under complex load are set up. The material constants are calculated by using the " XY " rectangle model. Referring to the Reissner variational principle, the nonlinear motion governing equations of the structure are deduced and resolved by the fourth-order Runge–Kutta method. The numerical results show that decreasing voltage and temperature and increasing volume ratio can delay the chaotic or multiple periodic motions of BNNT-reinforced piezoelectric plates, thus improving the dynamic stability of the structure.